So sánh giáo dục nghệ thuật cho trẻ mầm non ở 3 quốc gia: australia, Trung Quốc, Việt Nam - Lại, Vũ Kiều Trang (Tạp chí thiết bị giáo dục, 2023)
Education plays a key role in the formation and development of personality. Education in general and art education in particular is one of the important factors that help children develop both intelligence, personality and skills. This article presents an overview of research on art education for children in three countries: Australia, China and Vietnam. This study collects data from the authors who have analyzed the literature on the topic of art education for children in the following aspects: content of art education for preschool children; preschool class size; art education methods and the role of art education; thereby presenting an overview of art education in all three countries. The results show that: all three countries have shown interest in art education for preschool children, which is reflected in the content of drawing, dance, music and drama lessons; regulations on class sizes for children; variety of educational methods. Despite the similarities, countries still have differences when applied in practice.